2010
DOI: 10.1039/c002999h
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the analytical performance in RF-GD-OES for non-conductive materials by means of thin conductive layer deposition and the presence of a magnetic field

Abstract: Radiofrequency glow discharge coupled to optical emission spectrometry (RF-GD-OES) is a wellknown analytical technique for bulk, surface and depth profiling and can be applied in the direct analysis of conductors, semiconductors and non-conductors, however for the latter case limits still exist. The problem is related to the low power deposited in the plasma due to a voltage drop developing inside the material. The voltage transfer coefficient, defined as the ratio between the peak voltage at the front and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…17,18,22 Here, we demonstrate the effects of the magnetic field strength under different experiment conditions, namely, the discharge pressure and the rfpower.…”
Section: Optimization Of Parameters For Signal Enhancement Of the Stamentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,22 Here, we demonstrate the effects of the magnetic field strength under different experiment conditions, namely, the discharge pressure and the rfpower.…”
Section: Optimization Of Parameters For Signal Enhancement Of the Stamentioning
confidence: 99%
“…10,16 For a mass spectrometry, the sputtering rate and ionization efficiency play important roles in achieving the optimum analytical performance, 16 which could also be influenced by other factors such as gas pressure, rf-power, sample thickness, lattice binding energy of sample and so on. 17,18 With radio frequency (rf) discharges, nonconducting materials can be analyzed directly. However, the generator power is usually coupled capacitive to the plasma, so that the plasma power decreases with increasing thickness, thus sputtering rates, sensitivities and signal intensity decrease at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…In one, they discussed the use of pulsed RF-GD-OES for depth-profile quantification of metallic coatings. 303 In addition, the authors determined the effect of applying a magnetic field during the GD analysis and found that it offered the advantages of increased sputtering rates, better ionisation and better excitation efficiencies and, hence, an overall improvement in emission intensity was achieved. A comparison of emission intensities and emission yield parameters was made with the continuous mode of operation.…”
Section: 253mentioning
confidence: 99%
“…[5][6][7][8][9][10] Additionally, several methodological strategies, such as use of plasma gas mixtures, deposition of conductive thin layers, or magnetically boosted glow discharges, have been investigated using rf-GD spectroscopy to further enhance the analytical capabilities of this technique. [11][12][13][14][15] Particularly, in magnetically boosted GD, the combination of an external magnetic field and the electric field, applied between the anode and the cathode, causes modifications in the charged particle motion within the GD plasma. At the relatively low magnetic fields employed in glow discharge spectroscopy, only electron trajectories are significantly affected as ions are much heavier and their paths more difficult to alter.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 The magnetic field is usually applied by means of permanent magnets placed behind the sample, which implies that the magnetic field strength generated in the GD plasma is a function of the sample thickness. 11,26 Additionally, the application of axial magnetic fields with this experimental configuration significantly affects the produced crater shapes, which are more crowned, in detriment to the achieved depth resolution. 23,27 On the other hand, in transverse configuration the magnetic field is applied parallel to the sample surface and perpendicular to the axis along the cylindrical anode.…”
Section: Introductionmentioning
confidence: 99%